2020
DOI: 10.1186/s12935-020-1155-9
|View full text |Cite
|
Sign up to set email alerts
|

The novel long noncoding RNA CRART16 confers cetuximab resistance in colorectal cancer cells by enhancing ERBB3 expression via miR-371a-5p

Abstract: Background: Long noncoding RNAs (lncRNAs) have been shown to participate in multiple biological processes and confer drug resistance. However, it remains unclear whether lncRNAs are involved in conferring cetuximab resistance in colorectal cancer (CRC) cells.Methods: Cell Counting Kit-8 (CCK-8) assays were performed to assess the sensitivity of CRC cell lines to cetuximab treatment. -2 cells were stably transduced with cetuximab resistance-associated RNA transcript 16 (CRART16) or an empty vector using lentivi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
34
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(35 citation statements)
references
References 48 publications
1
34
0
Order By: Relevance
“…Signi cantly upregulated and downregulated miRNAs were also identi ed, such as miR-371a-5p (logFC = 7.62, p < < 0.001) and miR-122-5p (logFC=-3.87, p < < 0.001). Previous studies have revealed that miR-371a-5p can affects the MAPK signaling pathway, which is closely related to cell apoptosis and lipid metabolism [51,52]. In contrast, the overexpression of miR-371a-5p can promote the proliferation and metastasis of cancer cells [53].…”
Section: Discussionmentioning
confidence: 99%
“…Signi cantly upregulated and downregulated miRNAs were also identi ed, such as miR-371a-5p (logFC = 7.62, p < < 0.001) and miR-122-5p (logFC=-3.87, p < < 0.001). Previous studies have revealed that miR-371a-5p can affects the MAPK signaling pathway, which is closely related to cell apoptosis and lipid metabolism [51,52]. In contrast, the overexpression of miR-371a-5p can promote the proliferation and metastasis of cancer cells [53].…”
Section: Discussionmentioning
confidence: 99%
“…Elevated expression of HER3, a member of the EGF receptor family, has been reported to play an essential role in cancer progression and correlates with worse overall survival in many solid tumors 1 , 2 . Additionally, a number of studies revealed the upregulation of HER3 as an important resistance mechanism upon EGFR and HER2-targeted therapy 3 5 , emphasizing the importance in developing novel therapeutic strategies targeting HER3. HER3 comprises an impaired tyrosine kinase domain and requires heterodimerization with and transphosphorylation by other members of the EGFR family for activation and signaling 1 .…”
Section: Introductionmentioning
confidence: 99%
“…Colorectal cancer (CRC) is a prevalent malignancy of the digestive system. It is the third most common cancer worldwide and is ranked as the second cause of cancer‐related death 1,2 . Currently, surgical treatment, chemotherapy, and targeted therapy are the leading methods of CRC treatment and, with the continuous optimization of the treatment plan, the treatment effect continues to be improved 3 .…”
Section: Introductionmentioning
confidence: 99%